Pengembangan Modul Biologi Berbasis Problem Based Learning Siswa SMK Pertanian pada Materi Pewarisan Sifat - Adelima Dyah Kartika; Siti Zubaidah; Heru Kuswantoro (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The aim of this research and development was to examine the validity and practicality of problem based learning biology modules for High School students at Tulungagung. Based on the results of research on heterosis F1 soybean characterization resulting from crossing argomulyo varieties and CpMMV resistant lines. The learning module development model used is the ADDIE by Welty. The module feasibility assessment is assessed by namely practitioners, material experts and teaching materials experts, who are competent in their fields. Practical test through testing a small group of students using the questionnaire given. Overall, the results of module validation developed by material expert validators, module experts, and field practitioners in accordance with the aspects assessed and practicality tests obtain a good percentage, so that it can be concluded that the development of PBL-based modules on inheritance properties is stated very practical.Abstrak: Penelitian pengembangan ini bertujuan menguji kevalidan dan kepraktisan modul Biologi problem based learning siswa SMKN 1 Tulungagung. Berdasarkan hasil penelitian karakterisasi heterosis F1 kedelai hasil persilangan varietas argomulyo dan galur tahan CpMMV. Pembelajaran menggunakan modul dengan model ADDIE yang dikembangkan oleh Welty. Modul yang dikembangkan dinilai kelayakannya oleh validator ahli materi, ahli modul, dan praktisi lapangan yang sudah kompeten di bidangnya. Uji kepraktisan melalui uji kelompok kecil siswa menggunakan angket yang diberikan. Secara keseluruhan, hasil validasi modul yang dikembangkan oleh praktisi lapangan, ahli modul, dan materi sesuai dengan aspek yang telah dinilai serta dan uji kepraktisan memperoleh persentase yang baik sehingga kesimpulan yang diperoleh pengembangan modul Problem Based Learning Pewarisan Sifat dinyatakan sangat valid dan sangat praktis.